1967
DOI: 10.1021/jf60154a024
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom ninhydrin-positive compounds. Amino acids, related compounds, and other nitrogenous substances found in cultivated mushroom, Agaricus campestris

Abstract: A fraction, reactive to ninhydrin, was isolated from the edible, commercial mushroom, Agaricus campestris, by a novel isolation procedure. This isolate, when analyzed by an automatic amino acid analyzer, was found to contain amino acids, related compounds, and other nitrogenous substances heretofore undetected by previous investigators. The more important compounds definitely identified for the first time were -aminoadipic acid, ß-aminoisobutyric acid, canavanine, carnosine, creatinine, cystathionine, 2,4-diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…1) Soluble proteins from three strains of A. bisporus.-Several reports refer to the nutritional value and the relatively high percent of proteins in Agaricus bisporus (Altamura et al, 1967). Significant differences between the various amino acids in nine commercial strains of this mushroom were recently observed by Weaver et al (1977).…”
Section: Resultsmentioning
confidence: 99%
“…1) Soluble proteins from three strains of A. bisporus.-Several reports refer to the nutritional value and the relatively high percent of proteins in Agaricus bisporus (Altamura et al, 1967). Significant differences between the various amino acids in nine commercial strains of this mushroom were recently observed by Weaver et al (1977).…”
Section: Resultsmentioning
confidence: 99%
“…The taste of edible mushrooms is primarily attributed to several watersoluble substances, including 5 0 -nucleotides, free amino acids, and soluble carbohydrates (Altamura, Robbins, Andreotte, Long, & Hasselstrom, 1967;Chen, 1986;Craske & Reuter, 1965;Hac, Long, & Blish, 1949;Holts, 1971;Hommond & Nichols, 1975;Lin, 1988;Mau, Chyau, Li, & Tseng, 1997;Tseng & Mau, 1999). Craske and Reuter (1965) separated the amino acids present in an aqueous extract of Boletus edulis, and demonstrated that the most intense mushroom flavour was associated with highly basic amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Craske and Reuter (1965) separated the amino acids present in an aqueous extract of Boletus edulis, and demonstrated that the most intense mushroom flavour was associated with highly basic amino acids. Also, Altamura et al (1967) found that a series of novel free amino acids could be responsible for the characteristic flavour of Agaricus bisporus. Moreover, non-protein nitrogenous components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The application of mushroom preparations is ranked highly in traditional human medicine, and mainly originates from Chinese culture. From a nutritional point of view, mushrooms are useful since they contain numerous amino acids and vitamins, especially those of the B group, which play a signifi cant role in the regulation of metabolism in diabetic patients (Altamura et al, 1967;Chang, 1980;Crisan and Sands, 1978). In addition, they contain zinc, cobalt, vanadium and other oligo elements (Chang and Miles, 2004).…”
Section: Introductionmentioning
confidence: 99%